Animate Doll, Tropical Fetish: Structures of Race and Property in the Artisanal Folklore of Postcolonial Brazil - Gutiérrez, Jesús Alberto (Revista Literatura em Debate, 2019)
This article examines certain aesthetic dynamics through which the memory of transatlantic slavery finds a social incarnation in the realm of cultural production, and specifically in the traditional and popular arts. I take as an ethnographic case study the artisanal namoradeira doll, a folk genre of handcrafts that depict images of black women in a state of ambiguous agency. I consider how these figurines’ gendered representations of blackness stage a visual and literary relationship of affectable embodiment that allegorizes those early modern ontologies of property and personhood that licensed and administered colonial subjugation. Synthesizing a number of genealogies of the commodity form that turn on the historical and juridical figure of the slave, I argue that the dolls’ overdetermined figurations of racialized subjectivity do not simply affirm liberal conceptions of individuation and freedom, but rather enact a poetics that registers the internal contradictions that besiege this humanism.